Pancreatic imaging using diffusivity mapping - Influence of sequence technique on qualitative and quantitative analysis - Tavakoli, Andrej; Dreher, Constantin; Młynarska-Bujny, Anna; Kuder, Tristan Anselm; Gnirs, Regula; Schlemmer, Heinz-Peter; Bickelhaupt, Sebastian (Clinical imaging, 2022)
PURPOSE: To compare image quality of an optimized diffusion weighted imaging (DWI) sequence with advanced post-processing and motion correction (advanced-EPI) to a standard DWI protocol (standard-EPI) in pancreatic imaging. - MATERIALS AND METHODS: 62 consecutive patients underwent abdominal MRI at 1.5 T were included in this retrospective analysis of data collected as part of an IRB approved study. All patients received a standard-EPI and an advanced-EPI DWI with advanced post-processing and motion correction. Two blinded radiologists evaluated the parameters image quality, detail of parenchyma, sharpness of boundaries and discernibility from adjacent structures on b = 900 s/mm2 images using a Likert-like scale. Segmentation of pancreatic head, body and tail were obtained and apparent diffusion coefficient (ADC) was calculated separately for each region. Apparent tissue-to-background ratio (TBR) was calculated at b = 50 s/mm2 and at b = 900 s/mm2. - RESULTS: The advanced-EPI yielded significantly higher scores for pancreatic parameters of image quality, detail level of parenchyma, sharpness of boundaries and discernibility from adjacent structures in comparison to standard-EPI (p < 0.001 for all, kappa = [0.46,0.71]) and was preferred in 96% of the cases when directly compared. ADC of the pancreas was 7% lower in advanced-EPI (1.236 ± 0.152 vs. 1.146 ± 0.126 μm2/ms, p < 0.001). ADC in the pancreatic tail was significantly lower for both sequences compared to head and body (all p < 0.001). There was comparable TBR for both sequences at b = 50 s/mm2 (standard-EPI: 19.0 ± 5.9 vs. advanced-EPI: 19.0 ± 6.4, p = 0.96), whereas at b = 900 s/mm2, TBR was 51% higher for advanced-EPI (standard-EPI: 7.1 ± 2.5 vs. advanced-EPI: 10.8 ± 5.1, p < 0.001). - CONCLUSION: An advanced DWI sequence might increase image quality for focused imaging of the pancreas and providing improved parenchymal detail levels compared to a standard DWI.
Available online 10 December 2021
Gesehen am 30.08.2022